Distance-Energy Based Routing Algorithm with Priority Handling for UWSN - Prakash Gupta, Chandra; Bisht, Mayank; Kumar, Arun (International Journal of Sensors Wireless Communications and Control, 2013)
Underwater Sensor Networks (UWSNs) are being deployed for range of applications like collection of oceanic data for research, underwater exploration, surveillance, disaster prevention etc. UWSNs are different from terrestrial WSNs in terms of communication methods, network deployment and protocols used. In this paper, we present a localization based routing algorithm with distance and energy consideration. In our scheme, sender node selects a forwarding node on the basis of Routing Factor (Rf), a function of neighbor’s distance from destination node and its residual energy. Energy is scaled within a range to take heterogeneity of node energies into account. Priority packets and routing tables are also considered in our algorithm. Simulation results show improved performance of our routing algorithm in terms of network lifetime and end to end delays.
Keywords: routing factor